Distance and time effects in Swedish commodity prices, 1732-1914 - Mario J. Crucini; Gregor W. Smith (Queen's University, Department of Economics, 2016)
We study the role of distance and time in statistically explaining price dispersion across 32 Swedish towns for 19 commodities from 1732 to 1914. The resulting large number of relative prices (502,689) allows precise estimation of distance and time effects, and their interaction. We find an effect of distance that declines significantly over time, beginning in the 18th century, well before the arrival of canals, the telegraph, or the railway.
Keywords: N70; F61; E37; 330; distance effect; law of one price; Rohstoffpreis; Regionaler Preisindex; Preiskonvergenz; Geographische Entfernung; Verkehrsgeschichte; Schätzung; Schweden